Immunosuppressive therapy and acquired immunological disorders. - Kinlen, L (1992)
Impairment of the immune system by drugs, such as azathioprine and cyclosporin, or by diseases, such as AIDS, represents the most firmly established cause of non-Hodgkin's lymphoma (NHL). Neither drugs nor diseases, however, can explain the increases in the incidence of NHL in the general population, for these include cohorts relatively unexposed to immunosuppressive drugs or to AIDS. Furthermore, no immunological disorder that is associated with an increased risk of NHL is known to have increased in incidence. Among alternative explanations is the possibility of increased exposure to a lymphomagenic agent in the environment that acts by nonimmunological means. Pesticides and herbicides may belong to this category, but they will not explain the substantial increases in NHL in urban populations. However, the evidence of an underlying viral aetiology for the lymphomas in several different forms of immune impairment may be relevant to the increases in NHL in the general population. Paralytic poliomyelitis and mumps represent examples of diseases that have changed their pattern of occurrence in this century, consequent on changes in social conditions. It is therefore not impossible that changes in hygiene and in population density have altered the average age of exposure to a virus, thereby increasing the likelihood of a lymphomagenic effect.